2018
DOI: 10.1093/gbe/evy031
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Dark Matter Investigations: How Microbial Studies Transform Biological Knowledge and Empirically Sketch a Logic of Scientific Discovery

Abstract: Microbes are the oldest and most widespread, phylogenetically and metabolically diverse life forms on Earth. However, they have been discovered only 334 years ago, and their diversity started to become seriously investigated even later. For these reasons, microbial studies that unveil novel microbial lineages and processes affecting or involving microbes deeply (and repeatedly) transform knowledge in biology. Considering the quantitative prevalence of taxonomically and functionally unassigned sequences in envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
91
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(95 citation statements)
references
References 89 publications
1
91
0
3
Order By: Relevance
“…An ever-increasing number of genomes and metagenomes are unlocking uncharted regions of microbial diversity 1,8,9 , providing new perspectives on the evolution of life 10,11 . However, our rapidly growing inventories of new genes have a glaring issue: between 40% and 60% cannot be assigned to a known function [12][13][14][15] . Current analytical approaches for genomic and metagenomic data [16][17][18][19][20] generally do not include this uncharacterized fraction in downstream analyses, constraining their results to conserved pathways and housekeeping functions 17 .…”
Section: Introductionmentioning
confidence: 99%
“…An ever-increasing number of genomes and metagenomes are unlocking uncharted regions of microbial diversity 1,8,9 , providing new perspectives on the evolution of life 10,11 . However, our rapidly growing inventories of new genes have a glaring issue: between 40% and 60% cannot be assigned to a known function [12][13][14][15] . Current analytical approaches for genomic and metagenomic data [16][17][18][19][20] generally do not include this uncharacterized fraction in downstream analyses, constraining their results to conserved pathways and housekeeping functions 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Our definition is much stricter than previous definitions of the metagenomic dark matter which accepts remote homology to known sequences [23]. The need to include metagenomic dark matter in comprehensive analyses of the gut microbiome matches the arguments presented by Bernard et al in their recent manuscript on microbial dark matter where they opine that "unraveling the microbial dark matter should be identified as a central priority for biologists" [24].…”
Section: Introductionmentioning
confidence: 70%
“…Culture-based approaches to characterizing the subgingival microbiome spawned a slew of studies on individual bacteria, their responses to environmental shifts and their roles in disease causation as independent operators [42][43][44][45][46]. However, cultivation independent methods have revealed that polymicrobial diseases are caused by the collective actions and interactions of the microbiome [47,48], and that the "invisible" members of a microbial community have important contributions to these interactions [49,50]. When we used a top-down approach to map the genomic content of and the biological pathways encoded by the microbiomes associated with chronic, localized and generalized aggressive periodontitis, a surprising picture of the three phenotypes emerged.…”
Section: Discussionmentioning
confidence: 99%